Reviews (New blackfriars, 1966)
JESUS AND THE KINGDOM; THE ESCHATOLOGY OF BIBLICAL REALISM PARABLES OF JESUS; INTRODUCTION AND EXPOSITION THE COLLECTION: A STUDY IN PAUL'S STRATEGY CHRISTIANITY ACCORDING TO PAUL INTRODUCTION TO THE NEW TESTAMENT THE RULE OF QUMRAN AND ITS MEANING MAN'S PLACE IN NATURE HOMINISATION: THE EVOLUTIONARY ORIGIN OF MAN AS A THEOLOGICAL PROBLEM CREATIVE PERSONALITY IN RELIGIOUS LIFE. A HISTORY OF PROTESTANTISM. THE SPIRIT OF PROTESTANTISM